An innovative aluminization process for solid oxide cell interconnects: From the design to the processing and testing - E. Zanchi; H. Javed; S.De La Pierre; M. Ferraris; G. Cempura; A. Benelli; A.R. Boccaccini; F. Smeacetto (Materials & Design)
Applying an alumina-based coating at the sealant interface on interconnects can significantly reduce degradation and extend the lifetime of Solid Oxide Cell (SOC) stacks. This study introduces an innovative aluminization process achieved through Electrophoretic Deposition (EPD) of metallic aluminum powder on Crofer22APU stainless steel, reported here for the first time. The EPD suspensions and coating consolidation treatments were optimized for intermediate temperature applications in SOC stack interconnects. The alumina-based coating enhances steel resistance to high-temperature oxidation and improves the interface at the joined areas with the sealant by increasing surface roughness. Alumina-coated interconnect-glass sealant samples were subjected to static air ageing at 850 °C for up to 1000 h to evaluate interface evolution and potential corrosion product formation. The mechanical resistance of the alumina-coated steel joints, both in their initial state and after 1000-hour aging, was assessed via torsion tests, with a shear strength of 31.2 ± 2.0 MPa and 33.0 ± 1.0 MPa for as-prepared and aged samples, respectively, revealing a cohesive fracture mode and no interface degradation even after prolonged aging.